Pengaruh Perputaran Modal Kerja Perputaran Piutang, dan Perputaran Persediaan Terhadap Rentabilitas Ekonomi Perusahaan Sektor Perdagangan Eceran di Bursa Efek Indonesia - Anak Agung Ayu Mas Wasundari; Ni Nyoman Suriani (Universitas Warmadewa, 2021)
This study aims to determine the effect of working capital turnover, accounts receivable turnover, and inventory turnover simultaneously and partially on economic profitability. The research sample was 12 companies based on the purposive sampling technique. Data obtained from the website www.idx.co.id. Data analysis used multiple linear regression. The results show: (1) There is a significant influence between working capital turnover, accounts receivable turnover, and inventory turnover simultaneously on the economic profitability of retail trading companies listed on the Indonesia Stock Exchange in 2015-2018. (2) There is a significant influence between working capital turnover on the economic profitability of retail trading companies listed on the Indonesia Stock Exchange in 2015-2018. (3) There is a significant influence between the turnover of accounts receivable on the economic profitability of retail trading companies listed on the Indonesia Stock Exchange in 2015-2018. (4) There is no significant effect between inventory turnover on the economic profitability of retail trading companies listed on the Indonesia Stock Exchange in 2015-2018.